Allelopathic Effects of Sunflower Residue on Growth of Rice and Subsequent Wheat Crop - Bashir,Uzma (Instituto de Investigaciones Agropecuarias, INIA, 2012)
Sunflower (Helianthus annuus L.) is a well known allelopathic plant species. However, Pakistani farmers generally incorporate the sunflower residue in the soil with the aim to enhance soil fertility and organic matter. Field experiments were, therefore, carried out to evaluate the effect of sunflower residue incorporation on growth and yield of rice (Oryza sativa L.) and subsequent wheat (Triticum aestivum L.) crop. For rice crop, there were four treatments viz. control, sunflower residue incorporation (RI), NPK fertilizers, and NPK+RI. Two rice varieties (Basmati Pak and Basmati Super) were cultivated. Incorporation of sunflower residue markedly reduced plant growth and yield in ’Basmati Pak’. There was 34% reduction in yield of this variety due to RI. ’Basmati Super’ was tolerant to sunflower allelopathy, where the effect of RI was generally insignificant on plant growth and grain yield. Two commonly cultivated varieties of wheat (Inqalab 91 and Punjab 96) were sown in the same plots after harvesting the rice, without any addition of either RI or NPK. In ’Punjab 96’, the effect of RI or RI+NPK was insignificant on grain yield. In contrast, in ’Inqalab 91’, RI in combination with NPK fertilizers significantly reduced the grain yield by 41% as compared to NPK alone. The present study concluded that rice ’Basmati Super’ and wheat ’Punjab 96’ are suitable for cultivation under sunflower allelopathic stress.